DNA extraction with silica membrane column from teeth left in soil for more than 60 years. (December 2015) - Tsukada, K.; Harayama, Y.
Abstract: We performed DNA extraction from four teeth left in soil for more than 60 years by three methods (AP method, EP method and AEP method). DNA extraction was performed with QIAamp DNA Investigator Kit, DNA typing with AmpFlSTR Identifiler Plus PCR amplification Kit, and electrophoresis with the Applied Biosystems 3130xl Genetic Analyzer. The AEP method is highly efficient in extracting DNA from teeth left in soil for more than 60 years.